Dirasat in Economics and Business A Summary of a research design for the study of the state of Political Science in Arab Universities - SHEMBESH, ALI .M. (Dirasat in Economics and Business, 1979)
This research design is meant to be step forward in prepar. ing for a study examining the state of political studies in Arab Universities. Bearing this goal in mind, the writer has prepared a questionnaire to be sent to thirty five Arab Universities. The questionnaire was based on several hypotheses which will be tested against data obtained from the questionnaire. The author believes that the research design is very impor tant to this study as well as other political studies, for the de sign helps in clarifying concepts and stating expectations of the study. It also enables the researcher to introduce his as sumptions. Moreover, the importance of the research design emerges from the fact that through it the researcher can put his strategy and minor plans for research to test before starting in earnest.